Algis Mickūnas’s Philosophy of Eros - Junutytė-Galvanauskienė, Laura (Problemos, 2016)
This article discusses the main thesis of Algis Mickūnas’s philosophy of Eros, mostly elaborated in his book Summa Erotica. The topic of Eros is an integral part of problematic of cosmos developed by Mickūnas, that is closely related to the critique of Western modern ontology and all the concepts presupposed by it: the critique of subject, substance, reality, time, etc. Consideration of the phenomena of Eros in Mickūnas’s philosophy is inseparable from an attempt to liberate Eros from dualistic metaphysics determining reductions of Eros of one kind or another, such as desensualising or materialising it, and not allowing to experience it as all embracing the cosmic given. Eros should be understood as an envelopment of the environment, as penetrating atmosphere that itself does not have any properties or specialities but provides with expression and vitality all other planes instead. Immediate experience of expressions that is based on the analysis of a living body enables to reveal the wholeness and worldliness of erotic desire. Being the condition of every expression and supplying vitality to all other planes Eros beyond itself does not have any other source. Eros manifests itself as excessive energy that does not search for anything else except itself and does not have any direction and purpose. The analysis of Eros as a cosmic given in Mickūnas’s philosophy questions the conceptions of Eros in Plato and Freud that were fateful for Western culture, and invoking the experience of other life-worlds it provides us with a possibility to refer to Eros beyond the terms of idealization, sublimation and frustration.